"ØªÙ†ÙÙŠØ¯ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¨Ø±Ù†Ø§Ù…Ø¬ Ø§Ù„Ù„Ù‘ØºØ© Ø§Ù„Ù…ÙƒØ«Ù‘Ù Ù„Ù„Ø·Ù‘Ù„Ù‘Ø§Ø¨ Ø§Ù„Ø¬Ø¯ÙŠØ¯Ø© - M.alaika nasrulloh; ahmad zulfikri (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
Language Intensive Program is a form of effort and innovation on the campus of the Darussalam Islamic Institute of Blokagung to equip students' mastery of foreign languages, especially new students. This program is directly handled by the IAIDA campus Language Technical Implementation Unit (UPT-B). This effort is the latest innovation at the tertiary level which may rarely be applied in other campuses. In addition, this program is still relatively young because it has only been running for 3 semesters. As a new program, enabling innovation to occur, this program is still undergoing changes in response to emerging problems. So that in the future it is really able to equip students with quality foreign language competences. In this case, by using a descriptive approach, the writer wants to describe the process as well as the supporting and inhibiting factors for the implementation of Arabic learning which is packaged attractively in the Language Intensive Program in Campus institutions.